Development of a Model and Measurement Instrument for Structured/Processual Behavior - Dioquino, Manuel Jr C. (Philippine Management Review; Vol 9 (2001), 2016)
An instrument developed to measure a leader’s reaction to change and based upon a conceptualized continuum of structured versus processual behaviour is presented in this paper.  The responses of 146 managers from 7 companies were used to statistically validate the measurement tool.  The instrument has the potential for use by practitioners to determine who should lead change efforts and how they should lead these efforts